Polycentricity and metropolitan governance. A Swiss case study - Lars Glanzmann; Nathalie Grillon; Christian Kruse; Alain Thierstein (European Regional Science Association (ERSA), 2004)
The concept of `polycentric spatial development', a central principle of the European Spatial Development Perspective, is closely linked to the concept of `sustainable urban development'. But `polycentricity' has different significance at different spatial scales. Within a European context, polycentricity can refer to functional connectivity (supported by developments in ICT and transportation), between global “gateway” cities such as London, Paris and Frankfurt on the one hand, and the utilisation of global economic and knowledge flows coming into these cities for the benefit of other EU cities and regions on the other hand. At a finer geographical scale, ,polycentricity' refers to outward diffusion from major cities to smaller ones over a wide area, and focuses on the local linkages that arise from this process. POLYNET is a joint research program of eight European university institutes, funded by the EU program Interreg IIIB Northwestern Europe (NWE). The project is focusing attention on a new phenomenon as far as it refers to the polycentric `Mega-City-Region' in NWE which in turn is characterised by connectivity in an `information' or `network' society. POLYNET examines functional relationships and information flows (material/transportation and virtual/ICT) associated with service sector business activity (banking, insurance, law, accounting, advertising, logistics, management and design consulting) within and between eight major Northwest European polycentric `Mega-City-Regions': South East England; Delta Metropolis, Netherlands; Rhine-Main, Germany; Île-de-France; Dublin, Ireland; Northern Switzerland / Zurich; Rhine-Ruhr, Germany and Brussels, Belgium. The paper first presents the methodological and empirical approaches applied, secondly identifies the polycentric patterns of the European Metropolitan Region of Northern Switzerland / Zurich. A third section describes the analysis of connectivity and inter-relationship of the metropolitan region of Northern Switzerland with regard to other polycentric metropolitan regions. Section four presents an outlook on potential implications for sustainable management of the metropolitan region of Northern Switzerland.
Keywords: 330